Analisis Kemampuan Mahasiswa PGSD dalam Menyusun RPP dan Melaksanakan Pembelajaran melalui Mikroteaching - Evarince N.A. Amaral; Anggela F. Niis; Friyani I. Un; Aplonaris Bau; Aprilia R. Mau; Damian Puling; Yohanis Kristianus Tampani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the ability of students in the Primary School Teacher Education (PGSD) Study Program to develop Lesson Plans (RPP) and implement teaching through microteaching activities. The RPP serves as a crucial tool for prospective teachers in designing a systematic and measurable learning process, while microteaching functions as an effective teaching practice medium to develop students’ pedagogical skills. This research employed a qualitative descriptive method, with data collection techniques including observation, documentation, and interviews with final-year PGSD students enrolled in the microteaching course. The findings reveal that most students were able to develop lesson plans in accordance with the applicable curriculum formats (K13 and Merdeka Curriculum), including formulating learning objectives and outlining the sequence of learning activities. However, weaknesses were still found in formulating learning indicators, selecting appropriate models and methods, and integrating literacy, numeracy, and the elements of the Pancasila Student Profile. In implementing microteaching, students demonstrated mastery of the material and conducted learning activities in a structured manner. Nonetheless, some still faced challenges in classroom management, interactive communication, and the use of media and educational technology. The conclusion of this study indicates that PGSD students’ abilities in preparing lesson plans and conducting microteaching are in the “fairly good” category. However, they still require further guidance and training to be fully prepared as professional educators in the field. It is expected that through continuous evaluation and constructive feedback from lecturers, students can improve the quality of their lesson planning and teaching practices more optimally.